1989
DOI: 10.1093/jaoac/72.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Arsenic in Beer by Dry Ashing, Hydride Generation Atomic Absorption Spectroscopy

Abstract: A method has been developed for determination of arsenic in beer. Organic matter is destroyed by the dry-ashing technique, the ash is dissolved in HC1, and hydrides of arsenic are generated by addition of sodium borohydride prior to atomization in a flame-heated quartz cell and atomic absorption spectroscopy measurement. The analytical features of the method are detection limit 0.1 ng/g beer, precision 8%, and recovery 97 ± 7%. The arsenic contents of different brands from Spain and other European countries we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…As far as arsenic is concerned, historically beer from several breweries was linked with the incidence of arsenic poisoning in the Manchester area, arising from the use of contaminated sulphuric acid 25 at the beginning of the twentieth century. More recently, Cervera et al 9 analyzed the arsenic content of different brands from Spain and other European countries. All the samples respected the legal regulations of Spain.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As far as arsenic is concerned, historically beer from several breweries was linked with the incidence of arsenic poisoning in the Manchester area, arising from the use of contaminated sulphuric acid 25 at the beginning of the twentieth century. More recently, Cervera et al 9 analyzed the arsenic content of different brands from Spain and other European countries. All the samples respected the legal regulations of Spain.…”
Section: Resultsmentioning
confidence: 94%
“…Herce-Pagliai et al 22 found arsenic at a level of 1.5-12.4 μg/L. No differences were found between bottled and canned beers, as well as no correlation existed with the specific gravity of the beers 9 . The process employed in the production of alcohol free beers is reported to influence the level of the final arsenic species found in beer.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of ashing aid added to the sample (5 ml of a suspension of Mg(NO 3 ) 2 and MgO), corresponding to 31 mg/ml of Mg (II) in the HG apparatus reaction flask, was selected previously (Cervera et al 19896). In the present study it was confirmed that this minor concentration of Mg (II) accelerates mineralization of the samples, produces spongier ash, facilitates its dissolution and does not interfere with arsenic determination.…”
Section: Resultsmentioning
confidence: 51%
“…Calcium has many properties similar to those of magnesium, and is present in high concentrations in milk. Given the high capacity of magnesium for causing interference in HG (Cervera et al 19896), and in view of the high calcium content of milk (1200/tg/ml), it was decided to carry out an interference study by comparing calibration graphs for arsenic without calcium with calibration graphs obtained using different amounts of calcium (5,10 and 25 mg in the reaction flask). The statistical method used to estimate interference from calcium was multiple linear regression analysis performed by the BMDP1R program (Dixon et al 1988).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation